Third-Party Certification of Forest Management In Indonesia: Analysing Stakeholders' Recognition and Preferences - Santi Pratiwi; Agung Wibowo; Lukas Giessen (Jurnal Manajemen Hutan Tropika, 2015)
The existence of third-party forest and timber certification schemes in Indonesia has created benefits and challenges, mainly for forest industries. In the end, the interests and objectives of those industries will determine whether they decide to get certified and if so, what certification schemes they will use. This study analyses the stakeholder recognition of the competing forest legality and sustainability certification systems and describes the preferences for particular schemes based on stakeholder interests. Online questionnaires were distributed to relevant stakeholders, namely logging companies, wood processing industries, wood processing associations, auditors, academics, environmental organisations and government officials. The results indicate that there are different scheme preferences based on the stakeholder's interests. Sistem verifikasi legalitas kayu (SVLK) is the most frequently preferred scheme due to the simplicity of its requirements and the low cost of its certifying process, while the Forest stewardship council (FSC) is valued for its reputation and very high standards. Furthermore, lembaga ekolabel Indonesia (LEI) was least preferred because of its complexity and because it was unpopular with foreign end buyers, and the programme for the endorsement of forest certification (PEFC) was identified as being a complex scheme that was expensive and subject to high standards, and also appeared to have the least demand. Each scheme should be improved based on stakeholders' expectations, that their popularity with end buyers of timber products should be improved, and that this should be done in a way that allows logging and wood processing industries to choose freely the scheme that is most advantageous to them.